ThewizardLiz Motivational Content Analysis on YouTube: The Impact of Personal Branding and Presentation Style on Audience Engagement - Shatara, Khansa Farama; Maghfiroh, Ana; Asiyah, Siti; Atiek, Diyah; Indriastuti, Niken Reti (Universitas Muhammadiyah Surakarta, 2024)
As YouTube continues to grow as a prominent platform for content creation, understanding how successful creators engage their audiences becomes crucial. ThewizardLiz, known for her motivational content aimed at empowering young women, presents a unique case for examining the impact of personal branding and content delivery on viewer engagement. This study analyzes ThewizardLiz's YouTube videos, focusing on (1) the accuracy and relevancy of the content, and (2) the delivery style of the information presented. Through a qualitative content analysis of her three most-viewed videos, the study evaluates how ThewizardLiz's content fosters self-confidence and personal growth. The findings reveal that while the videos are highly motivational and resonate with viewers, they often lack scientific evidence, instead relying on widely accepted self-help principles and personal anecdotes. This research provides insights into the effectiveness of motivational content on YouTube and highlights the role of personal branding in cultivating a loyal audience.